Secure RSMA for CF-mMIMO Systems With Low-Resolution DACs - Zhang, Yao; Yang, Kaixi; Xia, Wenchao; Zhang, Jun; Ni, Yiyang; Lu, Weidang (IEEE wireless communications letters, 2024)
This letter presents an investigation into secure transmission in a downlink rate-splitting-aided cell-free massive multiple-input multiple-output system. By incorporating the low-resolution digital-to-analog converters and imperfect channel knowledge, we derive tight closed-form expressions for the data rate and secrecy rate under Ricean fading channels. Additionally, we formulate a power control problem with the objective of maximizing the weighted sum data rate, while ensuring a target secrecy rate for all user equipments. A path-following optimization algorithm is then proposed to determine its solution numerically. All theoretical analyses and the efficacy of the proposed algorithm are validated through extensive simulations.